2019
DOI: 10.1093/ndt/gfy407
|View full text |Cite|
|
Sign up to set email alerts
|

SGLT-2 inhibitors and GLP-1 receptor agonists for nephroprotection and cardioprotection in patients with diabetes mellitus and chronic kidney disease. A consensus statement by the EURECA-m and the DIABESITY working groups of the ERA-EDTA

Abstract: Chronic kidney disease (CKD) in patients with diabetes mellitus (DM) is a major problem of public health. Currently, many of these patients experience progression of cardiovascular and renal disease, even when receiving optimal treatment. In previous years, several new drug classes for the treatment of type 2 DM have emerged, including inhibitors of renal sodium–glucose co-transporter-2 (SGLT-2) and glucagon-like peptide-1 (GLP-1) receptor agonists. Apart from reducing glycaemia, these classes were reported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
127
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 183 publications
4
127
0
6
Order By: Relevance
“…By contrast, SGLT2i and some GLP-1RA were associated with improved cardiorenal outcomes. SGLT2i reduced cardiorenal risk in patients at high cardiovascular risk and in patients with DKD, as recently reported [44,45]. Cardiovascular and renal benefit is present despite only a modest reduction in weight and regardless of glycemic control.…”
Section: Antihyperglycemic Efficacy Of Glp-1ra In Patients With Dkdmentioning
confidence: 59%
“…By contrast, SGLT2i and some GLP-1RA were associated with improved cardiorenal outcomes. SGLT2i reduced cardiorenal risk in patients at high cardiovascular risk and in patients with DKD, as recently reported [44,45]. Cardiovascular and renal benefit is present despite only a modest reduction in weight and regardless of glycemic control.…”
Section: Antihyperglycemic Efficacy Of Glp-1ra In Patients With Dkdmentioning
confidence: 59%
“…On the other, the longer life expectancy of the population and the increasing prevalence of risk factors for CKD such as obesity, diabetes and hypertension, together with the underdeveloped therapeutic armamentarium, are driving up the prevalence and impact of CKD. There is hope in the recent characterization of a dramatic nephroprotective impact of sodium-glucose transport protein 2 (SGLT2) inhibitors when added on top of renin angiotensin system (RAS) blockade for diabetic kidney disease and potentially other kidney diseases [4][5][6]. However, data from the hypertension field have clearly demonstrated that the availability of effective drugs is not enough, especially in polymedicated populations, where guidelines now emphasize measures to facilitate compliance [7].…”
mentioning
confidence: 99%
“…Furthermore, they will evaluate whether this renal protection also occurs independently of the presence of diabetes and thus of the glucose status. If yes, this will of course open new perspectives for the use of SGLT2s in patients with CKD and the interest for this pharmacological class might be increasingly shifted from endocrinologists to nephrologists [23,43], in a similar way as the expected shift to cardiologists as already mentioned [21].…”
Section: Renal Diseasementioning
confidence: 90%
“…The positive results on cardiovascular and renal outcomes profoundly influence the most recent consensus statement by the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) [20]. In the meantime, other societies of cardiology [6,21,22] and nephrology [23] also published new algorithms for the management of patients with T2DM at high risk of cardiovascular (including HF) and renal complications.…”
Section: Introductionmentioning
confidence: 99%